Calculation scheme of ground freezing depth in Terskol - Frolov Д. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
During the construction of avalanche-retaining geotechnical structures in mountainous areas comes up the problem of fixing and stability of these structures in conditions of seasonal and/or long-term freezing of the ground. This paper evaluates the influence of snow cover and air temperature on the depth of freezing and soil stability based on the developed calculation scheme for the winter seasons 2015/16-2019/20 in the Elbrus region. The calculation scheme was based on the problem of thermal conductivity of a three-layer medium (snow, frozen, and thawed soil) with a phase transition at the boundary. The heat balance equation included the energy of the phase transition, the inflow of heat from the thawed ground and the outflow to the frozen ground, and, in the presence of snow cover, through it to the atmosphere.